M-shaped beam profile output from an off-axis relay-imaging eight-pass Nd:glass laser preamplifier - Xie, Xudong; Yao, Ke; Zhou, Shouhuan (Frontiers in Physics, 2023)
In ultra-high-power/energy solid-state Nd:glass laser facilities, the gain distribution of the main amplifier system (MAS) is nonuniform owing to strong amplified spontaneous emissions in the MAS. A shaped beam profile from a preamplifier (PreAMP) should be set opposite to the gain profile in the MAS to obtain a high-power beam with an approximately flat beam profile. This flat beam profile can result in the high efficiency of the frequency-conversion crystals. In this study, the laser beam was spatially formatted as an M-shaped beam with precompensation (PreCOM) for the nonuniform gain profile of the MSA. Modulation of the cross-sectional gain distribution of the PreAMP was demonstrated by selecting the absorption coefficient of the Nd:glass rod and pump configuration. Using the proposed off-axis relay-imaging eight-pass amplifier, an M-shaped beam with an output pulse energy of 1 J and a repetition rate of 1 Hz was experimentally achieved. With an Nd 3+ concentration of 1.2 wt% and Nd: glass rod diameter of 18 mm, an M-shaped beam profile with a 4.3:1 ratio of intensity at the margin to that at the center was successfully obtained. Such controllable M-shaped beams can be optionally introduced to the MAS to compensate for non-uniform spatial gain profiles.